Manajerial Keuangan dalam Pengelolaan Pajak berlandaskan Sistem Informasi Akuntansi pada Perusahaan Swasta di Semarang - Jaluanto Sunu Punjul Tyoso; Amsar Amsar; Elly Yulianti (Journal Of Business, Finance, and Economics (JBFE), 2024)
This study analyzes financial management in a private company in Semarang through information management systems in payroll administration. The data were divided into five categories: general, finance, accounting, sales administration, and accounting. The analysis method used was information system analysis with five steps, including monitoring, business processes, task delegation, independent verification, and capture procedures. The business process involves several entities in the application of VAT, Income Tax Article 21, and Income Tax Article 23. The delegation of tasks is considered ineffective because the number of employees is not proportional to the volume of work, which has a negative impact on the company's revenue. Supervision is carried out by the payroll department to ensure data accuracy. Supporting factors for the use of information management systems include information technology, user-friendly systems, top management support, and employee expertise. Conversely, inhibiting factors include lack of funds, declining number of tax employees, and ineffective division of tasks. An independence verification process was also conducted to ensure compliance with the prevailing tax laws in Indonesia.